An Analysis of the Religious Anthropology Perspective in the Historical Texts of Thaqafi, Kufi, and Qazvini Razi - Tahereh Nazari ilkhani abadi; Mojtaba Garavand; Dariush Nazari (تاریخ نگری و تاریخ نگاری, 2023)
As an interdisciplinary approach, religious anthropology examines the position of man in relation to the divine teachings. This concept has found a distinct form in the Imami tradition, especially from the point of view of the idea of the "perfect man" and its connection with the religious system. Using a descriptive-analytical method, the present study attempts to answer the question of how the reflection of religious anthropology is formulated in two important Imami texts, namely Al-Gharat by Ibrahim ibn Muhammad Thaqafi Kufi (283 AH) and Al-Naqz by Abdul Jalil Qazwini Razi (560 AH). Despite the difference in the intellectual orientation of these two authors, Thaqafi as a hadith scholar and Qazwini as a theologian, both used history as a tool to present the image of the religious man and defend Shi'i identity on three common axes: identity- formation based on reason and ethics, use of historical narratives, and interaction with social contexts.  Al-Gharat’s emphasis on moral coherence and the tendency of negation towards a religious approximation indicate the transition of the Imami discourse towards an interactionist perspective. In this framework, the perfect human being is a multidimensional being who plays a reforming role in society through reason, morality and sharia. The authors based on rationality have outlined two complementary paths: the intra-religious path with the consolidation of Shiite identity and the extra-religious path with the tendency towards multicultural dialogue. In their view, history is not simply a narrative of events, but an epistemological tool for explaining human and saving values, and meanwhile the concept of “perfect man" as a comprehensive model of human” perfection occupies a central place in the Imamiyya epistemological system.